Dissemination of LED grow light radiation technology to accelerate hydroponic plant growth in Sidomulyo hydroponics in Perhentian Marpoyan Village, Marpoyan Damai District, Pekanbaru City - Rafil Arizona; Kurnia Hastuti; Eddy Elfiano; Jhonni Rahman; Shandy Kurniadi (Peneliti Teknologi Teknik Indonesia, 2022)
This research-based community service program aimed to create a series of LED grow lights for the “Sidomulyo Hydroponics” business, which increased hydroponic plant growth and improved the quality and quantity of hydroponic plants. The activity included creating a series of UV LED grow lights with radiation technology that stimulated the hydroponic plants' growth to help increase the harvest period, quality, and quantity of the plants (mustard). The methods used in implementing this research-based service were tool and material preparation, circuit design and ultraviolet LED grow light radiation setting, material and training presentation, and examination of the effect of UV grow light radiation on hydroponic plants. Experiments revealed that growing mustard plants under LED grow lights is one week faster, including harvest time.